Genome-wide association meta-analysis identifies two novel loci associated with dental caries - Shun Nogawa; Satoru Morishita; Kenji Saito; Hisanori Kato (BMC, 2024)
Abstract Background Tooth loss significantly impacts oral function and overall health deterioration. Dental caries and periodontal disease are major contributors to tooth loss, emphasizing the critical need to prevent these conditions. Genetic studies have played a crucial role in deepening our understanding of the underlying mechanisms of these diseases. While large-scale genome-wide association studies (GWAS) on dental caries and periodontal disease have been conducted extensively, research focusing on Asian populations remains limited. Given substantial genetic and lifestyle variations across ethnicities, conducting studies across diverse populations is imperative. This study aimed to uncover new insights into the genetic mechanisms of these diseases, contributing to broader knowledge and potential targeted interventions. Methods We conducted a GWAS using genome data from 45,525 Japanese individuals, assessing their self-reported history of dental caries and periodontal disease. Additionally, we performed a meta-analysis by integrating our results with those from a previous large-scale GWAS predominantly involving European populations. Results While no new loci associated with periodontal disease were identified, we discovered two novel loci associated with dental caries. The lead variants of these loci were intron variant rs10974056 in GLIS3 and intron variant rs4801882 in SIGLEC5. Conclusion Our study findings are anticipated to advance understanding of the underlying mechanisms of dental caries and periodontal disease. Thes insights may inform better management strategies for patients affected by these conditions.